Spin-off Strategy for Sharia Business Units of Conventional Commercial Banks in Indonesia Post-P2SK Law (Omnibus Law) - T. Rizkan Polem; Muhammad Ramadhan; Muhammad Yafiz (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The spin-off of Sharia Business Units (UUS) from conventional commercial banks isa strategic policy to strengthen the Islamic banking industry in Indonesia. Theenactment of the Financial Sector Development and Strengthening Law (UU P2SK)has shifted the spin-off policy approach from a mandatory one to a more flexible onebased on institutional readiness. This change emphasizes that the success of a spin-offis no longer determined solely by regulatory obligations, but rather by the ability ofeach UUS to prepare its institutional aspects comprehensively. Thus, the mainchallenge shifts to how to formulate an appropriate, realistic, and sustainable spin-offstrategy in accordance with the internal and external conditions of the institution. Thisstudy aims to identify factors influencing the spin-off process and formulate the mostappropriate strategy within the post-UU P2SK policy framework. The approach usedis a quantitative exploratory approach using the Analytic Network Process (ANP)method to analyze the interrelationships between factors and determine optimalstrategic priorities. The results indicate that the most dominant factors in determiningthe success of a spin-off are the commitment of controlling shareholders andmanagement. This factor is followed by capital and asset readiness, human resourcequality and readiness, regulatory support, information technology capabilities, andmarket and industry conditions. Given the limited institutional capacity, particularly atRegional Development Bank (BPD) UUS, a spin-off strategy through a Bank BusinessGroup (KUB) scheme is the most realistic option for institutional strengthening.Meanwhile, a full spin-off into a Sharia Commercial Bank (BUS) remains the long-termgoal once all necessary preparations are optimally met.